Electronic Measurements and Instrumentation. - Kishore, K. Lal. (2009)
Electronic Measurements and Instrumentation provides a comprehensive blend of the theoretical and practical aspects of electronic measurements and instrumentation. Spread across eight chapters, this book provides a comprehensive coverage of each topic in the syllabus with a special focus on oscilloscopes and transducers. The key features of the book are clear illustrations and circuit diagrams for enhanced comprehension; points to remember that help students grasp the essence of each chapter; objective-type questions, review questions, and unsolved problems provided at the end of each chapter, which help students prepare for competitive examinations; solved numerical problems and examples are provided, which enable the reader to understand design aspects better and to enable students to comprehend basic principles; and summaries at the end of each chapter that help students recapitulate all the concepts learnt.
7.3.1 Factors that Affect the Performance of a Transducer.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books